Dielectric surface passivation for silicon solar cells: A review - Bonilla Osorio, R; Hoex, B; Hamer, P; Wilshaw, P (Wiley, 2017)
Silicon wafer solar cells continue to be the leading photovoltaic technology, and in many places are now providing a substantial portion of electricity generation. Further adoption of this technology will require processing that minimises losses in device performance. A fundamental mechanism for efficiency loss is the recombination of photo-generated charge carriers at the unavoidable cell surfaces. Dielectric coatings have been shown to largely prevent these losses through a combination of different passivation mechanisms. This review aims to provide an overview of the dielectric passivation coatings developed in the past two decades using a standardised methodology to characterise the metrics of surface recombination across all techniques and materials. The efficacy of a large set of materials and methods has been evaluated using such metrics and a discussion on the current state and prospects for further surface passivation improvements is provided.